BreedCat i-Care: the development of breeder cat care mobile application / Nur Fazlen Idayu Jaharuddin - Jaharuddin, Nur Fazlen Idayu (2019)
All animals, including breed cat, need to be cared and loved. However, not much attention is given to breed cat. Therefore, this project, which is BreedCat i-Care mobile application is intended to teach the cat owner on how to take care of their breed cat. The objectives of this project are to identify the user requirement for BreedCat i-Care mobile application, to design and develop the breedCat i-Care by following the Mobile Development Life Cycle (MADLC) methodology during the development process. This mobile application will be used Android Studio software with java programming to provide an efficient application. In addition, to make this mobile application be more interesting, the multimedia elements is included such as video-based audio. Furthermore, BreedCat i-Care mobile application have provide platform to find the breeders within Shah Alam area using geolocation. Last but not least, based on the results of testing phase, it shows that this project will benefits several parties such as the breed cat owners as this mobile application will help them to learn on how to take care of breed cat interactively, the designer and developers will develop the mobile application that brings benefits to the community. For future recommendation, this mobile application can also be used in iOS platform and can add more value of interactive element such as 360 degrees videos to get attraction from users.